Leakage Vortex Progression through a Guide Vane’s Clearance Gap and the Resulting Pressure Fluctuation in a Francis Turbine - Nirmal Acharya; Saroj Gautam; Sailesh Chitrakar; Chirag Trivedi; Ole Gunnar Dahlhaug (Energies, 2021)
A clearance gap (CG) between guide vanes (GVs) and facing plates exists at both ends of a Francis turbine and allows the opening angle to be adjusted for varying operating conditions. Leakage flow is induced through this gap due to the pressure difference between the two sides of the guide vanes. While some research works have used qualitative approaches to visualize and predict the strength of a leakage vortex (LV), this paper presents a method for quantifying vortices along a trajectory. In this paper, a prototype high-head Francis runner with specific speed of 85.4 is considered as a reference case. A systematic investigation across both space and time is carried out, i.e., analysis of the spatial temporal progression of LV for three operating conditions. While travelling from the CG to runner leading edge, LV evolution and trajectory data are observed and the values of vorticity and turbulent kinetic energy are calculated for the LV trajectory. Frequency spectrum analyses of pressure oscillations in the vaneless space, runner blade, and draft tube are also performed to observe the peak pressure pulsation and its harmonics. Unsteady fluctuations of the runner output torque are finally studied to identify the patterns and magnitudes of torque oscillations.